Lymphoepithelioma-like carcinoma of the skin: An exceedingly rare primary skin tumor - Ramesh Kumar Kushwaha; Suresh Kumar Jain; H B Abhinandan; Dinesh Baheti (Wolters Kluwer Medknow Publications, 2015)
Primary lymphoepithelioma-like carcinoma of the skin (LE-lCS) is a very rare cutaneous malignancy of uncertain origin. The neoplasm reveals typical morphological similarity to undifferentiated nasopharyngeal carcinoma (lymphoepithelioma). This case report presents a 47-year-old man with a 5 mm erythematous papule on dorsal nose of six months duration. The patient underwent complete surgical excision and is disease free 7 months later.